Comparative Analysis of MCDM Methods in Employee Award Ranking - Roznim binti Mohamad Rasli; Mesran Mesran; Ridha Maya Faza Lubis (PDSI, 2026)
Awards are an important form of appreciation for outstanding employees, but the process of selecting recipients is often faced with various challenges, especially in assessing subjective aspects of performance. To overcome this, the Multi-Criteria Decision Making (MCDM) method can be an effective solution. MCDM offers a systematic framework for evaluating various alternatives (in this case, employees) based on a number of relevant criteria. By using the MCDM method, the process of selecting award recipients can be carried out more objectively and transparently. Some commonly used MCDM methods, such as MAUT, OCRA, and CoCoSo, have their own advantages and disadvantages. This study aims to compare the three methods specifically in the context of selecting employee award recipients. The final results obtained show that the best alternative is A6, where the results of the three methods look the same position or location in the ranking. After a comparative analysis of the three methods, it can be concluded that the OCRA method is the best method in terms of ranking consistency compared to the other two methods. Thus, it is hoped that recommendations for the most suitable MCDM method can be obtained to be applied in similar situations